Potential applications of curcumin and its novel synthetic analogs and nanotechnology-based formulations in cancer prevention and therapy - Batra Surinder K; Mimeault Murielle (BMC, 2011)
Abstract Curcumin has attracted great attention in the therapeutic arsenal in clinical oncology due to its chemopreventive, antitumoral, radiosensibilizing and chemosensibilizing activities against various types of aggressive and recurrent cancers. These malignancies include leukemias, lymphomas, multiple myeloma, brain cancer, melanoma and skin, lung, prostate, breast, ovarian, liver, gastrointestinal, pancreatic and colorectal epithelial cancers. Curcumin mediates its anti-proliferative, anti-invasive and apoptotic effects on cancer cells, including cancer stem/progenitor cells and their progenies, through multiple molecular mechanisms. The oncogenic pathways inhibited by curcumin encompass the members of epidermal growth factor receptors (EGFR and erbB2), sonic hedgehog (SHH)/GLIs and Wnt/β-catenin and downstream signaling elements such as Akt, nuclear factor-kappa B (NF-κB) and signal transducers and activators of transcription (STATs). In counterbalance, the high metabolic instability and poor systemic bioavailability of curcumin limit its therapeutic efficacy in human. Of great therapeutic interest, the selective delivery of synthetic analogs or nanotechnology-based formulations of curcumin to tumors, alone or in combination with other anticancer drugs, may improve their chemopreventive and chemotherapeutic efficacies against cancer progression and relapse. Novel curcumin formulations may also be used to reverse drug resistance, eradicate the total cancer cell mass and improve the anticarcinogenic efficacy of the current anti-hormonal and chemotherapeutic treatments for patients with various aggressive and lethal cancers.